L'identité sociale : mieux se connaître pour diriger les autres - Hannum, Kelly (Guides "Transformer les idées en action.", 2012)
The context of leadership has changed. Traditionally, leaders worked in organizations in which people largely shared a common culture and set of values. Today, leaders must bring together groups of people with very different histories, perspectives, values, and cultures. The people you lead are likely to be different from you and from each other in significant ways. Leaders today need an awareness of social identity, their own and that of others.